2017
DOI: 10.15829/1560-4071-2017-10-33-41
|View full text |Cite
|
Sign up to set email alerts
|

Complex Evaluation of the Significance of Populational Genetic Markers Associated With Myocardial Infarction and Risk Factors

Abstract: Цель. Оценить использование комплексной оценки информативности в Рос-сийской популяции генетических маркеров инфаркта миокарда, идентифици-рованных в полногеномных ассоциативных исследованиях. Материал и методы. Группа больных ИМ (200 человек) и контрольная группа (420 человек) были сформированы на основе популяционной выборки 45-69 летних жителей г. Новосибирска (9400 человек), которая была собрана в ходе работы по международному проекту HAPIee. Пациенты с инфарктом мио-карда, поступившие в блок интенсивной т… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
1
5
1
4
Order By: Relevance
“…Our study revealed an association of the G allele of rs1333049 with TC and LDL-C levels among males. These data contradict some other studies [10,11,33], for example, Ellis et al have demonstrated a correlation of the C/C genotype with higher TG and TC levels in blood [26]. The study by Ellis et al was performed on patients with ischemic heart disease (New Zealand), whereas our study deals with the general population.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Our study revealed an association of the G allele of rs1333049 with TC and LDL-C levels among males. These data contradict some other studies [10,11,33], for example, Ellis et al have demonstrated a correlation of the C/C genotype with higher TG and TC levels in blood [26]. The study by Ellis et al was performed on patients with ischemic heart disease (New Zealand), whereas our study deals with the general population.…”
Section: Discussioncontrasting
confidence: 97%
“…Our study confirmed the association of rs1333049 with myocardial infarction in the general population; this finding is consistent with the results of studies on some groups of patients in Russia [11,12,35] and abroad [35,36,37,38].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Исследовали генетические маркеры: rs619203, rs10757278, rs1333049, rs499818, rs1376251, rs4804611, rs17465637, rs2549513. Исследуемые однонуклеотидные последовательности (ОНП), ассоциированы с развитием ИБС, что ранее было подтверждено международными полногеномными исследованиями [8,9]. В наших предыдущих работах по оценке годичных исходов ОКСпST и ОКСбпST также была выявлена взаимосвязь перечисленных ОНП с вероятностью развития неблагоприятного прогноза с помощью разработанной модели прогнозирования риска [10,11].…”
Section: Conflictsunclassified
“…Известно, что эпидемиология и особенности течения заболеваний связаны не только со средовыми, социальными и культурными факторами, но и с генетическими особенностями, индивидуальными для каждого отдельного этноса. Именно поэтому в последние годы исследования генетической компоненты предрасположенности к ИБС проводятся на разных этнических когортах [7][8][9].…”
unclassified